2021
DOI: 10.1007/s00198-021-05957-9
|View full text |Cite
|
Sign up to set email alerts
|

How can the orthopedic surgeon ensure optimal vitamin D status in patients operated for an osteoporotic fracture?

Abstract: In this narrative review, the role of vitamin D deficiency in the pathophysiology, healing of fragility fractures, and rehabilitation is discussed. Vitamin D status can be assessed by measuring serum 25(OH)-vitamin D level with standardized assays. There is a high prevalence of vitamin D insufficiency (25(OH)D < 50 nmol/l (i.e., 20 ng/mL)) or deficiency (25(OH)D < 25 nmol/l (i.e., 10 ng/mL)) in patients with fragility fractures and especially in those with a hip fracture. The evidence on the effects of vitamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 149 publications
0
8
0
Order By: Relevance
“…Also, indirect evidence to support such supplementation is poor as studies in traumatic or fragility fractures are scarce. 102 We have therefore no information on the impact of low Vitamin D levels or poor calcium intake on the course of active CNO.…”
Section: Rationalementioning
confidence: 99%
See 1 more Smart Citation
“…Also, indirect evidence to support such supplementation is poor as studies in traumatic or fragility fractures are scarce. 102 We have therefore no information on the impact of low Vitamin D levels or poor calcium intake on the course of active CNO.…”
Section: Rationalementioning
confidence: 99%
“…We could not identify intervention studies on possible beneficial effects of vitamin D and calcium supplementation in active CNO. Also, indirect evidence to support such supplementation is poor as studies in traumatic or fragility fractures are scarce 102 . We have therefore no information on the impact of low Vitamin D levels or poor calcium intake on the course of active CNO.…”
Section: Recommendationsmentioning
confidence: 99%
“…73 Specifically, vitamin D and calcium supplementation is known to improve BMD and muscle strength, and to reduce falls and fractures in adults deficient in these nutrients. 74 Furthermore, several observational studies have found a correlation between higher protein intake and higher retention of lean muscle mass and BMD in the elderly. 75,76 Creatine supplementation has also been observed to increase the benefits of endurance exercise in healthy individuals, although the effect in clinical populations with compromised muscle and bone health has yet to be determined.…”
Section: How To Counteract Os?mentioning
confidence: 99%
“…However, it seems reasonable to suggest that some forms of hip fracture in older populations that are often not treated for possible osteoporotic risk 24 may derive some independent or collective benefit from vitamin D supplementation as far as reducing hip fracture incidence rates as well as mortality rates or further fractures post hip fracture surgery in vulnerable older adults. [24][25][26][27][28] In combination with silicon a recent basic study has revealed some degree of vitamin D influence on bone structure restoration and improved calcium absorption that appears to offer a possible avenue for enhancing bone related regeneration and that may prove valuable to examine further in the realm of hip fracture prevention and that is supported by human clinical evidence, [29][30][31][32] even though its presence may not impact number of falls or injurious falls that often lead to hip fractures. 33 However, there are multiple contrary study findings as well as multiple design problems that remain in this body of research, even though more favorable potentially relevant clinical findings prevail than not.…”
Section: Specific Observationsmentioning
confidence: 99%